An Effectiveness Study of a Digital Mindfulness-Based Program for Upper Secondary Education Students - Lahtinen, Oskari; Salmivalli, Christina (Mindfulness, 2020)
Objectives Mindfulness-based programs/interventions (MBPs) are emerging as treatments for anxiety and stress for adults and adolescents. MBPs can also be helpful as universal interventions for healthy subjects. Few studies have looked at how beneficial MBP effects transfer to digital MBPs. Methods The study was a randomized controlled trial with 1349 participants aged mostly 16–19. We compared a digital MBP vs. a waitlist condition. Online questionnaire data were collected pre-program, post-program, and at 3-month follow-up. Results Completing the MBP resulted in a small-to-moderate reduction in anxiety ( F 1,681 = 13.71, p < .01, d = .26), a small reduction in depression ( F 1,686 = 8.54, p < .01, d = .15), and a small increase in psychological quality of life ( F 1,708 = 3.94, p = .05, d = .16). Attrition rate for the MBP was 41.5%. Conclusions The results suggest that digital MBPs can be successful in delivering at least some of the benefits characteristic of face-to-face MBPs.